Biosynthesis of Indole-3-Acetic Acid by New Klebsiella oxytoca Free and Immobilized Cells on Inorganic Matrices. (1st May 2012) - Celloto, Valéria R.; Oliveira, Arildo J. B.; Gonçalves, José E.; Watanabe, Cecília S. F.; Matioli, Graciette; Gonçalves, Regina A. C.
Abstract : While many natural and synthetic compounds exhibit auxin-like activity in bioassays, indole-3-acetic acid (IAA) is recognized as the key auxin in most plants. IAA has been implicated in almost all aspects of plant growth and development and a large array of bacteria have been reported to enhance plant growth. Cells of Klebsiella oxytoca isolated from the rhizosphere of Aspidosperma polyneuron and immobilized by adsorption on different inorganic matrices were used for IAA production. The matrices were prepared by the sol-gel method and the silica-titanium was the most suitable matrix for effective immobilization. In operational stability assays, IAA production was maintained after four cycles of production, obtaining 42.80 ± 2.03  μg mL −1 of IAA in the third cycle, which corresponds to a 54% increase in production in relation to the first cycle, whereas free cells began losing activity after the first cycle. After 90 days of storage at 4 ° C the immobilized cells showed the slight reduction of IAA production without significant loss of activity.